2014
DOI: 10.1016/j.jviscsurg.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Endpoints in cancer clinical trials

Abstract: Endpoints are measurable clinical and biological findings that are used for the development and assessment of treatment options. In the treatment of cancer, endpoints can be classified into two categories: "patient-centered clinical endpoints" including overall survival (OS) and health-related quality of life (QoL), and "tumor-centered clinical endpoints" such as progression-free survival. Surrogate endpoints are tumor-centered clinical endpoints that can be used as substitutes for patient-centered clinical en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 31 publications
1
73
0
4
Order By: Relevance
“…The correlation between objective response rate (ORR), time to progression, disease-free survival, or progressionfree survival (PFS) and OS is poorly understood [76,79]. Some studies investigating ICBs in NSCLC, RCC, HNSCC, and UC have demonstrated increased OS in the absence of a PFS benefit [27,28,31,42,47,57], whereas other trials in melanoma and NSCLC have demonstrated increased OS, as well as ORR and PFS, compared with standard of care (Table 2) [23,43].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
“…The correlation between objective response rate (ORR), time to progression, disease-free survival, or progressionfree survival (PFS) and OS is poorly understood [76,79]. Some studies investigating ICBs in NSCLC, RCC, HNSCC, and UC have demonstrated increased OS in the absence of a PFS benefit [27,28,31,42,47,57], whereas other trials in melanoma and NSCLC have demonstrated increased OS, as well as ORR and PFS, compared with standard of care (Table 2) [23,43].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
“…whether to exclude the primary site by means of specifically recording regional control (RC). Despite the published Consolidated Standards of Reporting Trials (CONSORT) best practice guidelines, to date there is no common agreement on this term [33,34].…”
Section: Locoregional Control (Lrc)mentioning
confidence: 99%
“…The difference to PFS is that TTP does not include deaths. It may only be used when the event of interest is solely disease progression, and investigators have to be aware of the fact that TTP does differ from PFS in this very aspect [34]. Unfortunately, TTP and PFS are still frequently used interchangeable by investigators [27].…”
Section: Time To Progression (Ttp)mentioning
confidence: 99%
“…A member of the medical team administered the two QoL questionnaires to the patient. Our methodology for QoL questionnaire administration complied with the users' guide of the two questionnaires [2,12]. Indeed, for QUAL-E, it was necessarily a member of the medical team who interviewed and recorded the patient's responses.…”
Section: Data Collectionmentioning
confidence: 99%
“…Equivalence or non-inferiority trials to control for toxicity and to assess deescalating doses are increasingly required. This is why taking into account another patientcentered outcome rather than tumor-centered endpoints seems a good alternative [2]. Health-related quality-of-life (HRQL) has become the second endpoint in clinical research in cancer to demonstrate clinical benefits of new treatments for patients [3].…”
Section: Introductionmentioning
confidence: 99%